Cultivation and characterization of spirochetes from cerebrospinal fluid of patients with Lyme borreliosis. - Karlsson, M (1990)
Attempts were made to culture spirochetes from cerebrospinal fluid samples of 105 patients suspected of having Lyme borreliosis with neurological complications. At the final evaluation, only 38 patients fulfilled the criteria of neuroborreliosis. Spirochetes were cultured from cerebrospinal fluid samples of four of these patients. All four patients had pleocytosis in their cerebrospinal fluid and a history of neurological symptoms of only 4 to 10 days in duration. Two of them had no detectable antibodies against any of the isolated spirochetes in their cerebrospinal fluid, both when tested with an enzyme-linked immunosorbent assay and when tested by immunoblotting. An antibody reaction against the homologous isolate that was distinctly stronger than that against the heterologous isolates was found in the serum and cerebrospinal fluid samples from one patient. The cells of the isolates were morphologically similar and showed a very similar protein pattern when analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Cells of all isolates reacted with the monoclonal antibodies H5332 and H9724, which also react with Borrelia burgdorferi B31, the type strain. One isolate lost a major protein of 23 kilodaltons after subcultivation for 4 months. We conclude that isolation of spirochetes from cerebrospinal fluid might prove successful in clinically selected cases of Lyme borreliosis.